SISTEM INFORMASI ABSENSI PADA PT. POS INDONESIA KANTOR WILAYAH USAHA POS IV JAKARTA - Frans Edward Schaduw (Paradigma, 2014)
PT . POS INDONESIA Jakarta business area IV is a big company engaged in the field of services and has many parts . In each section consists of many employees Here the authors see with so many personnel will require good attendance system . Once the authors refer to the attendance is there still using signatures attendance . Trying authors using the waterfall method to see how to analyze the existing problems in the existing manual attendance at these services firm by interviewing and questioning the assistant manager of human resources services and direct observation of activities studied . Here can be seen at the time of manufacture rekab absent very time consuming lama.Setelah the author tries to design phase , here the authors use a tool that is a data flow diagram data for designing how the system of making data flow information needed for absentee company 's services . So did the author use to design normalized tables and fields are required for building information systems absentee PT . Pos Indonesia Jakarta Region IV effort . In attendance system will be able to see out the inclusion of employees with more detail , as well as the human resources department to see employee who is absent at the desired date and can see the recap missed months with very clear that recap absent sick , do not get in , overtime with very precise , accurate and fast . So that reporting to the other parts that need to be very fast tersajinya attendance reporting . With the absence of this information system will help a lot of PT . Pos Indonesia Jakarta Region IV businesses and can help managers to make decisions to improve the performance of the company employees